Integration team members' approaches to uncertainty management in M&A - Diduc (Sniazhko), Sniazhana (Elsevier, 2022)
Mergers and acquisitions (M&A) are associated with various uncertainties. Often, large companies designate integration team members to organize post-acquisition integration. However, little is known about what integration team members do in the post-acquisition integration process. This study examines how integration team members deal with uncertainties in post-acquisition integration, specifically how they manage tensions that require different and conflicting approaches. The research is based on an in-depth qualitative case study that examines the post-acquisition integration phase in real-time in the context of two Nordic firms. The study offers three main findings. First, among various uncertainty reduction, coping and balancing approaches observed in this study, the balancing approach emerged as a new method to face uncertainty. The second finding illustrates that the choice among various uncertainty management methods and their approaches is a dynamic process, in which integration team members from both buying and acquired firms are actively involved. Lastly, the study identifies that integration team members use collaboration as the way to address tensions in uncertainty management.
Keywords: collaboration; Integration manager; Integration team members; Post-acquisition integration; Uncertainty management; fi=Henkilöstöjohtaminen|en=Human Resource Management|